Epigenetic Regulation of Excitatory Amino Acid Transporter 2 in Neurological Disorders - Alam, Mohammad Afaque; Datta, Prasun K. (Frontiers in Pharmacology, 2019)
Excitatory amino acid transporter 2 (EAAT2) is the predominant astrocyte glutamate transporter involved in the reuptake of the majority of the synaptic glutamate in the mammalian central nervous system (CNS). Gene expression can be altered without changing DNA sequences through epigenetic mechanisms. Mechanisms of epigenetic regulation, include DNA methylation, post-translational modifications of histones, chromatin remodeling, and small non-coding RNAs. This review is focused on neurological disorders, such as glioblastoma multiforme (GBM), Alzheimer’s disease (AD), amyotrophic lateral sclerosis (ALS), Parkinson’s disease (PD), bipolar disorder (BD), and neuroHIV where there is evidence that epigenetics plays a role in the reduction of EAAT2 expression. The emerging field of pharmaco-epigenetics provides a novel avenue for epigenetics-based drug therapy. This review highlights findings on the role of epigenetics in the regulation of EAAT2 in different neurological disorders and discusses the current pharmacological approaches used and the potential use of novel therapeutic approaches to induce EAAT2 expression in neurological disorders using CRISPR/Cas9 technology.